PENGGUNAAN ALAT KB PADA WANITA KAWIN DI PERDESAAN DAN PERKOTAAN (Studi Hasil SDKI 2017 Provinsi Gorontalo) - Syamsul Syamsul; Bala Bakri; Hizry Stevany Limonu (Jurnal Kependudukan Indonesia, 2020)
The Indonesia and Demographic Health Survey (IDHS) in 2017 reported a gap between urban and rural contraceptive use in Gorontalo Province, Indonesia. This urban-rural inequality calls for an exploration of its drivers. Hence, this study aims at reviewing the literature to analyze the level of use of contraception for married women in rural and urban areas by examining several factors, such as education, knowledge, age, occupation, information provision, and source of service. The main data source used for this study is 2017 IDHS Report, Gorontalo Province section. The results shows that despite a higher knowledge of contraception in urban married women than their rural counterpart, modern contraceptive use is higher in rural areas than in urban areas. Moreover, provision of information plays a larger role in contraceptive use compared to other aspects. Furthermore, the low contraceptive use among urban women is due to the limited services, where there is a mismatch between the needs and the availability of contraception.